2021
DOI: 10.32615/ps.2021.005
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous salicylic acid ameliorates waterlogging stress damages and improves photosynthetic efficiency and antioxidative defense system in waxy corn

Abstract: Highlights • Two waxy corn inbred lines were used in this study • Exogenous SA mediated physiological and photosynthetic adaptation • Exogenous SA alleviated the waterlogging-induced damages of waxy corn seedlings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
0
17
0
4
Order By: Relevance
“…These results are mostly consistent with those of previous studies [ 13 , 17 , 25 , 56 , 57 ]. For instance, according to Maity et al [ 25 ], concentrations of nitrate reductase, superoxide dismutase, catalase and peroxidase improved the response to pomegranate plant sprayed with 300 ppm SA after 120 d. Data also revealed that the leaf defense enzymes activities were enhanced visibly when the aboveground plant parts were treated with various SA concentrations at multiple time points [ 5 , 12 , 27 , 30 , 51 , 58 ]. It was suggested in some study that the leaf superoxide dismutase and peroxidase activities were elevated after 36 h following the exogenous spraying of 0.5~4.0 mM SA on Capsicum annuum L. and after 4, 8, 12, 16, 24, 32, 36 and 48 h following the exogenous spraying of SA (0.5, 1.0, 2.0, 3.0 and 4.0 mM) on Capsicum annuum L. [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are mostly consistent with those of previous studies [ 13 , 17 , 25 , 56 , 57 ]. For instance, according to Maity et al [ 25 ], concentrations of nitrate reductase, superoxide dismutase, catalase and peroxidase improved the response to pomegranate plant sprayed with 300 ppm SA after 120 d. Data also revealed that the leaf defense enzymes activities were enhanced visibly when the aboveground plant parts were treated with various SA concentrations at multiple time points [ 5 , 12 , 27 , 30 , 51 , 58 ]. It was suggested in some study that the leaf superoxide dismutase and peroxidase activities were elevated after 36 h following the exogenous spraying of 0.5~4.0 mM SA on Capsicum annuum L. and after 4, 8, 12, 16, 24, 32, 36 and 48 h following the exogenous spraying of SA (0.5, 1.0, 2.0, 3.0 and 4.0 mM) on Capsicum annuum L. [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant chemical defense responses against biotic and abiotic stress can be activated by the application of exogenous hormones to the aboveground parts of plants. Examples of exogenous hormones that can enhance plant defense responses include jasmonic acid (JA), indole acetic acid (IAA), salicylic acid (SA) and others [ 1 , 2 , 3 , 4 , 5 ]. SA is one of the ubiquitous endogenous signal molecules in plants that can activate defense and protection mechanisms for disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Growth parameters were measured in accordance with an earlier study (Wang et al, 2021). Shoot height and leaf dimensions were measured using a ruler.…”
Section: Determination Of Growth Parametersmentioning
confidence: 99%
“…56 With an application of exogenous SA, the carotenoid content in flooded maize plants increased significantly, the stomatal conductance was regulated, and the photosynthetic capacity of PSII with the actual electron transfer quantum efficiency of PSII were significantly improved. 41,57 Spraying SNP on cotton leaves 10 days after waterlogging relieved FWS through increasing the chlorophyll content, photosynthetic rate, and the intensity of light energy absorbed by plants. 45 There have been many related research reports on the chemicals used as ECs to improve photosynthesis in various application methods and optimal concentrations (Table 8).…”
Section: ■ Exogenous Chemicals Used For Alleviating Flooding/waterlog...mentioning
confidence: 99%